Gene Expression Analysis of Pediatric Acute Myeloid Leukemia Identified a Hyperactive ASXL1/BAP1 Axis Linked with Poor Prognosis and over Expressed Epigenetic Modifiers. (7th September 2021) - Elyamany, Ghaleb; Akhter, Ariz; Kamran, Hamza; Rizwan, Hassan; Shabani-Rad, Meer-Taher; Alkhayat, Nawaf; Al Sharif, Omar; Elborai, Yasser; Al Shahrani, Mohammad; Mansoor, Adnan
Abstract: Genetic aberrations in the epigenome are rare in pediatric AML, hence expression data in epigenetic regulation and its downstream effect is lacking in childhood AML. Our pilot study screened epigenetic modifiers and its related oncogenic signal transduction pathways concerning clinical outcomes in a small cohort of pediatric AML in KSA. RNA from diagnostic BM biopsies (n = 35) was subjected to expression analysis employing the nCounter Pan-Cancer pathway panel. The patients were dichotomized into low ASXL1 (17/35; 49%) and high ASXL1 (18/35; 51%) groups based on ROC curve analysis. Age, gender, hematological data or molecular risk factors (FLT3 mutation/molecular fusion) exposed no significant differences across these two distinct ASXL1 expression groups (P > 0.05). High ASXL1 expression showed linkage with high expression of other epigenetic modifiers (TET2/EZH2/IDH1&2). Our data showed that high ASXL1 mRNA is interrelated with increased BRCA1 associated protein-1 (BAP1) and its target gene E2F Transcription Factor 1 (E2F1) expression. High ASXL1 expression was associated with high mortality 10/18 (56%) vs. 1/17; (6%) P < 0 .002. Low ASXL1 expressers showed better OS 740 days vs. 579 days; log-rank P= < 0.023; HR 7.54 (0.98-54.1). The association between high ASXL1 expression and epigenetic modifiers is interesting but unexplained and require further investigation. High ASXL1 expression is associated with BAP1 and its target genes. Patients with high ASXL1 expression showed poor OS without any association with a conventional molecular prognostic marker.